Deep learning based educational transformation as a roadmap to indonesia emas 2045 - Afriani Salman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The Indonesia Emas 2045 vision emphasizes educational transformation to cultivate globally competitive human resources. This conceptual study, employing a qualitative library research design and content analysis of key academic and policy literature, proposes Deep Learning as a strategic pedagogical shift from rote memorization to prioritizing conceptual understanding and real world application. Key findings confirm deep learning is an indispensable response to pervasive national foundational learning deficits and acts as a vital mechanism for fostering essential 21st century competencies and ethical character. Deep learning is crucial for effectively leveraging the demographic dividend. However, large scale implementation faces systemic challenges, particularly in teacher readiness and digital infrastructure gaps. As rekomendation, a cohesive national strategy focusing on intensive upskilling and fundamental assessment reform is vital to position deep learning as the primary pillar for developing globally competitive human capital.